Convergence of Monetary Transmission in EMU New Evidence - Linda A. Toolsema; Jan-Egbert Sturm; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper examines how the pass-through of monetary policy measures in 6 EMU countries has evolved over time and whether there is convergence in monetary transmission. The countries included are: Belgium, France, Germany, Italy, the Netherlands and Spain, and the sample period is 1980-2000. We conclude that major differences in pass-through exist in our sample, both in terms of initial as well as long-run responses to policy-induced interest rate changes. There is no indication for convergence of monetary policy transmission.
Keywords: 330; Monetary transmission; pass-through; interest rate stickiness; EMU